A design method of radial fans considering the torque-speed-characteristic of the motor - Epple, Philipp; Miclea, Mihai; Pfannschmidt, Klaus; Grobeis, Detlev; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2010)
The use of high speed radial impellers is very common in fans for industrial applications. The most common design case is the one with constant speed. In that case, one assigns the corresponding value to the speed n, hence the speed no longer matters in the further design procedure: it is given and it is constant. However, in many cases the speed is not constant, since it is governed by the torque-speed characteristic of the driving motor. In such a case it is necessary to consider the motor characteristic already at the design stage. In the present work a design method was developed in order to perfectly match the torque-speed characteristic of the radial impeller to the torque-speed characteristic of the driving motor. In such a way it is possible to design an impeller-motor unit with maximum efficiency. The extended impeller mean-line-design formulas presented in Epple [6] were complemented with the equations describing the motor torque-speed-characteristic. Both sets of equations where combined and solved in order to achieve a prescribed operating range at a maximum efficiency. In order to validate the design method, it was applied to an industrial fan which should be improved. That radial fan with spiral casing consisted of the main radial fan and a motor cooling axial fan at the other end of the shaft. This later fan was rotating at a too low speed leading to cooling problems of the motor. Hence, a new fan had to be designed which had to deliver the same hydraulic performance but at higher rotating speeds. This had to be done, however, on the given motor. That could only be done when properly designing an impeller matching its torque-speed characteristic to the torque-speed characteristic of the motor: it was an excellent task to validate the combined impeller-motor design procedure. Under these constrains six designs where performed and validated with a commercial CFD solver. The three best designs according to the CFD results were built as prototypes and measured at a standard test rig. The best design delivered the prescribed head-flow characteristic at an even improved hydraulic efficiency. The higher speed was also properly achieved. The design procedure is described and explained in detail and a detailed CFD analysis is presented, complemented by the experimental data obtained at the test rig. A final comparative analysis of the combined impeller-motor design method, the CFD analysis and the measurements is presented. Copyright © 2010 by ASME.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.adesig
Keywords: CFD; Impeller-motor matching; Radial impeller design; Test rig measurements; Torque-speed-characteristic